Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have the following inequality, which (supposedly) holds for every $x\in\mathbb{R}$:

$$ 1+x\ln\left(x+\sqrt{1+x^{2}}\right)\geq\sqrt{1+x^{2}} $$ I've been struggling to find some known inequalities involving logarithms that could be applied here (and lack of condition for $x$ to be non-negative doesn't help either). I would be very helpful for hints on how this should be approached.

share|cite|improve this question
Try taking everything over to the left hand side and differentiate the result. – Mark Bennet Aug 13 '12 at 20:38
You can simplify the manipulation rather by setting $y=\sqrt{1+x^2}$ and noting that $\frac {dy}{dx} = \frac x y$ – Mark Bennet Aug 13 '12 at 20:45
up vote 4 down vote accepted

Just to illustrate the trick for differentiating in my comment, using the same $f(x)$ as Norbert but writing $y=\sqrt{1+x^2}$:$$f(x)=1+x\log(x+y)-y$$ and knowing that $$\frac{dy}{dx}=\frac x y$$ we compute:

$$f'(x) = 0 + \log(x+y) +\frac {x (1+\frac x y)} {x+y} -\frac x y $$

And simplify ... which works neatly essentially for the same reason that Davide Giraudo's substitution works, to give first and second derivatives which are easy to work with:

So we get $$f'(x) = \log(x+y)$$ and $$f''(x)=\frac {1+\frac x y} {x+y}=\frac 1 y$$

We find that there is a minimum at $x=0$ with $f(0)=0\text{ and } f''(x) \text { positive throughout, which gives us what we need ...}$

share|cite|improve this answer
OK, now I understand your method too. Thank you! – Johnny Westerling Aug 13 '12 at 21:45

Hint 1: Set $f(x)=1+x \log(x+\sqrt{1+x^2})-\sqrt{1+x^2}$

Hint 2: Find stationary points from equation $f'(x)=0$.

Hint 3: Check that $f''(x)>0$ for all $x\in\mathbb{R}$

Hint 4: Conclude that $f$ attains its minimum, check that it equals $0$.

share|cite|improve this answer
Thank you for the answer. Although your method gives us a clear and certain answer, because of the sheer length of the second-order derivative of $f$, I assume that there is some quicker (though maybe less intuitive) way to prove this. – Johnny Westerling Aug 13 '12 at 21:00

Write $x=\sinh t$. Then we have to proove that $1+\sinh t\ln(\sinh t+\cosh t)\geq \cosh t$, that is $$\forall t\in\Bbb R,1+\sinh t\times t\geq \cosh t.$$ Since $$1-\cosh t=-\frac 12\left(e^{t/2}-e^{—t/2}\right)^2=-2\sinh^2\frac t2,$$ we have to show that $$\forall t\in\Bbb R,\sinh t\times t\geq 2\sinh^2\frac t2,$$ that is $$\forall t\geq 0, t\cdot \cosh\frac t2\geq\sinh\frac t2\Leftrightarrow\forall t\geq 0, f(t):=2t\cosh t-\sinh t\geq 0. $$ We have $f'(t)=\cosh t+2t\sinh t\geq 0$, hence $f$ is increasing. Since $f(0)=0$, we can conclude.

share|cite|improve this answer
Thanks! I understand it, until the moment where we move from $\forall_{t\in\mathbb{R}},\sinh{t}\cdot{t}\geq{2}\sinh^{2}\frac{t}{2}$ to the next line. Could you please explain this transition? – Johnny Westerling Aug 13 '12 at 21:32
I replaces $1-\cosh t$ by what I computed in the last line. – Davide Giraudo Aug 13 '12 at 21:33
I think I understand your method as well... Thanks! – Johnny Westerling Aug 13 '12 at 22:04

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.